When tribalism meets liberalism: Human rights and Indigenous boundary problems in Canada - Gover, Kirsty (University of Toronto Law Journal, 2014)
This article draws on debates about the ‘boundary problem’ in democratic theory to consider the normative challenges raised by descent-based Aboriginal membership rules in Canada. The boundary paradox is one of the most intractable puzzles of democratic theory. If a demos is necessarily bounded, so that some people are excluded, what normative principle could justify these exclusions? Liberal theory tends to insist on the primacy of consent as the basis of political society and so fails to explain the reliance of liberal democracies on birthright membership, especially the distribution of citizenship to foreign-born descendants of citizens. Applied to expressly kinship-based polities like Aboriginal communities, liberal approaches prioritize non-discrimination, potentially denying to those communities the capacity to distribute membership by reference to characteristics listed as ‘prohibited grounds’ in human rights law, including, most problematically, race and ethnicity. The article outlines the parallels between Canadian citizenship law, the Indian Act regime, and First Nations’ membership codes, and examines the distinctive role to be played by section 35 of Canada’s Constitution Act 1982 in tempering non-discrimination logics. It concludes that existing justificatory tests (the ‘valid legislative object’ test, and the section 1 ‘reasonable limits’ test) are unlikely to provide a way forward, but that a promising methodology can be discerned in Canadian law and policy, in which the ‘reasonableness’ of Aboriginal descent–based exclusions is assessed relative to the characteristics of a free and democratic Aboriginal community. I suggest that this adaptation of liberal non-discrimination norms is an expression of the continuing importance of kinship and descent boundaries in settler-state constitutionalism. Although many questions remain to be resolved, Canadian human rights laws and methodologies could assist in the primary challenge posed to settler-state political theory: the reconciliation of tribal and liberal forms of political organization.